Green Defense and Environmental Accountability: Comparative Study between Indonesia and ASEAN Member States (RechtJiva, 2025)
This study examines the intersection between environmental protection and national defense policies in ASEAN countries, focusing on Indonesia’s approach to integrating environmental responsibility within military activities. The concept of green defense emphasizes sustainable military operations that minimize ecological impact while maintaining national security readiness. Using a normative juridical and comparative approach, this research analyzes legal frameworks, defense regulations, and environmental policies across Indonesia, Malaysia, and the Philippines. The findings highlight that while Indonesia has integrated environmental elements in its Non-Warfare Military Operations (OMSP), institutional coordination and enforcement mechanisms remain weak compared to neighboring countries. Strengthening legal accountability and regional cooperation under ASEAN’s environmental framework is crucial to achieving environmentally responsible defense practices.